STRATEGI PEMASARAN PRODUK MUDHARABAH DALAM MENINGKATKAN NASABAH DI PT. BPRS MENTARI PASAMAN SAIYO SIMPANG EMPAT - Intan Permata Sari; Rusyaida (CV. ADIBA AISHA AMIRA, 2025)
This research is motivated by the small number of customers of mudharabah financing products compared to other financing products at BPRS and competition with other financial institutions that have similar products. This study aims to determine the marketing strategy of mudharabah financing products applied by PT BPRS Mentari Pasaman Saiyo Simpang Empat in increasing the number of customers. The method used is descriptive qualitative research with data collection techniques through observation, interviews and documentation. The results of this study indicate that the marketing strategy at PT BPRS Mentari Pasaman Saiyo uses the 7P marketing mix: product, price, place, promotion, people, process and physical evidence. Of the 7 elements of the marketing mix, there are 3 elements that have been implemented and run optimally, namely product, price and location strategies, while promotions, people (HR), service processes and physical evidence have been running but are still less optimal than the other 3 elements. The main obstacles in implementing this strategy are the low understanding of the community about mudharabah financing, the lack of collateral or collateral from customers and the high competition between financial institutions.